Komunikasi Persuasif Esi Dalam Membangun Minat Menjadi Pemain Profesional Esports Di Kabupaten Karawang - Daniel Fernando Halomoan Situmorang; Zainal Abidin; Rastri Kusumaningrum (Peneliti.net, 2023)
This study aims to identify and examine ESI's persuasive communication strategies in building an interest in becoming a professional esports player in Karawang district. The theory used is the theory of perception which is built on four dimensions, namely communicators who have high credibility, messages, environmental influences, and understanding and continuity of a message. This study used descriptive qualitative method. Data collection techniques were carried out by triangulation which included interviews, observation and documentation studies, then the data were analyzed through three stages namely reduction, presentation and conclusion of data. The results of the research and discussion show that people's perceptions of their interest in becoming professional esports players through persuasive communication carried out by ESI Karawang are not optimal even though ESI Karawang often holds esports competitions and monitors esports athletes, but messages uploaded via ESI Karawang's social media do not exist which contains the main ideas regarding the development of community potential for the world of esports.